UNIQUENESS THEOREMS FOR MULTIPLE FRANKLIN SERIES - Navasardyan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
It is proved, that if the square partial sums $σ_{q_n}(x)$ of a multiple Franklin series converge in measure to a function $f$, the ratio $\dfrac{q_{n+1}}{q_n}$ is bounded and the majorant of partial sums satisfies to a necessary condition, then the coefficients of the series are restored by the function $f$.
Keywords: majorant of partial sums, $A$-integral, uniqueness.